Manajemen Budaya Sekolah dalam Implementasi Penguatan Pendidikan Karakter di Sekolah Berbasis Islam - Anisa Kurnia Lestari; Imron Arifin; Sunarni Sunarni (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purposes of the study were: to find out the management of school, to find out the implementation of strengthening character education, to find out the obstacles and solutions of school culture management in the implementation of strengthening character education at Al Hasyimiyyah Elementary School and Al Manar Elementary School. The data in this study were obtained based on the result of interviews with school principals, curriculum, teachers, students and parents or students’ guardians. The schools were chosen since they meet the criteria in the research, which is Islamic-based schools. The results obtained from the research are: (1) Al Manar Elementary School and Al Hasyimiyyah Elementary carry out school culture management starting from the planning, organizing, implementation to evaluation stages; (2) the implementation of strengthening character education in Al Manar and Al Hasyimiyyah is related to a school culture that has been chosen by the school through the implementation of the school culture that has been selected. Strengthening character education is formed by schools as early as possible. (3) the schools faced some external and internal factors or obstacles, one of which is the lack of cooperation with parents at home to supervise students.Abstrak: Penelitian ini bertujuan untuk mengetahui manajemen budaya sekolah, implementasi penguatan pendidikan karakter, kendala dan solusi manajemen budaya sekolah dalam implementasi penguatan pendidikan karakter di SD AlHasyimiyyah dan SD Al Manar. Metode yang digunakan dalam peneltian ini yaitu metode penelitian kualitatif deskriptif. Data dalam penelitian ini diperoleh berdasarkan hasil wawancara dengan kepala sekolah, kurikulum, guru, peserta didik dan orangtua atau wali murid. Kedua sekolah yang dijadikan tempat penelitian merupakan sekolah yang berbasis Islam sesuai dengan kriteria dalam penelitian. Hasil yang diperoleh dari penelitian, meliputi (1) sekolah Al Manar dan Alhasyimiyyah melakukan manajemen budaya sekolah mulai dari tahap perencanaan, pengorganisasian, pelaksanaan hingga tahap evaluasi; (2) implementasi penguatan pendidikan karakter di sekolah Almanar dan Alhasyimiyyah berkaitan dengan budaya sekolah yang sudah dipilih oleh sekolah melalui pelaksanaan budaya sekolah yang telah dipilih. Penguatan pendidikan karakter dibentuk sedini mungkin oleh sekolah; (3) ada beberapa faktor eksternal dan internal atau kendala yang dialami oleh sekolah salah satunya kurangnya kerja sama dengan orangtua di rumah untuk mengawasi peserta didik.